Iws1 and Spt6 Regulate Trimethylation of Histone H3 on Lysine 36 through Akt Signaling and are Essential for Mouse Embryonic Genome Activation - Oqani, Reza K. (Sci Rep, 2019)
The mRNA processing and export factor, Iws1, interacts with the histone H3/H4 chaperone, Spt6 (Supt6 in mouse gene ontology) and recruits the lysine methyltransferase, Setd2, to chromatin to regulate H3K36me3. This recruitment is known to be crucial for pre-mRNA splicing and Iws1 has been shown to interact with REF1/Aly to mediate mRNA export. However, the role of this complex has not yet been examined in embryonic development. Here, we show that knockdown of either Iws1 or Supt6 blocked embryo development, primarily at the 8/16-cell stage, indicating that Iws1 and Supt6 are crucial for mouse preimplantation development. In the knockdown embryos, we observed decreases in pre-mRNA splicing, mRNA export and the expression of the lineage-specific transcription factor, Nanog. We found that either Iws1 or Supt6 are required for H3K36 trimethylation and that concurrent knockdown of both Iws1 and Supt6 blocks embryonic development at the 2-cell stage. We show that H3K36me3 is modulated by the Pi3k/Akt pathway, as inhibition of this pathway reduced the global level of H3K36me3 while activation of the pathway increased the level of this modification in 2-cell embryos. We observed that Iws1 interacts with nuclear Akt in early embryos, and herein propose that Akt modulates H3K36me3 through interaction with Iws1. Together, our results indicate that the Iws1 and Supt6 play crucial roles in embryonic genome activation, lineage specification, and histone modification during mouse early development.